2007
DOI: 10.1007/s00203-007-0320-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol (PEG)–carboxylate–CoA synthetase is involved in PEG metabolism in Sphingopyxis macrogoltabida strain 103

Abstract: Sphingopyxis macrogoltabida strain 103 possesses polyethylene-glycol (PEG)-inducible pegBCDAE operon encoding the genes relevant to PEG degradation. PEG is converted to PEG-carboxylate by PegA (PEG dehydrogenase) and PegC (PEG-aldehyde dehydrogenase). In this study, the recombinant PegE (homologous to acyl-CoA synthetases) was characterized. PegE was an acyl-CoA synthetase active for PEG-carboxylate and fatty acids. Judging from the nature of this kind of protein (located on the cytoplasmic membrane as a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Some metabolic‐associated genera were observed significantly increased by tributyrin supplementation in SBM‐based diet, including Hydrogenophaga , Rhodocyclaceae , Sphingopyxis , Hydrogenophaga , Methyloversatilis and Devosia . The increase in denitrifying species, such as Hydrogenophaga (Magic‐Knezev, Wullings, & Kooij, ; Tanamool, Imai, Danvirutai, & Kaewkannetra, ) , Rhodocyclaceae (Oren, ) and Methyloversatilis (Smalley et al, ) and bacteria degrading organic substances, such as Sphingopyxis (Tani, Somyoonsap, Minami, Kimbara, & Kawai, ), may contribute to degrading ingredients from SBM protein. Although these results provided basic knowledge on the impacts of dietary tributyrin supplementation alteration on the intestinal microbiota composition and diversity of juvenile yellow drum, putative involvement of bacteria in the metabolism and immunity merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metabolic‐associated genera were observed significantly increased by tributyrin supplementation in SBM‐based diet, including Hydrogenophaga , Rhodocyclaceae , Sphingopyxis , Hydrogenophaga , Methyloversatilis and Devosia . The increase in denitrifying species, such as Hydrogenophaga (Magic‐Knezev, Wullings, & Kooij, ; Tanamool, Imai, Danvirutai, & Kaewkannetra, ) , Rhodocyclaceae (Oren, ) and Methyloversatilis (Smalley et al, ) and bacteria degrading organic substances, such as Sphingopyxis (Tani, Somyoonsap, Minami, Kimbara, & Kawai, ), may contribute to degrading ingredients from SBM protein. Although these results provided basic knowledge on the impacts of dietary tributyrin supplementation alteration on the intestinal microbiota composition and diversity of juvenile yellow drum, putative involvement of bacteria in the metabolism and immunity merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Methyloversatilis (Smalley et al, 2015) and bacteria degrading organic substances, such as Sphingopyxis (Tani, Somyoonsap, Minami, Kimbara, & Kawai, 2008), may contribute to degrading ingredients from SBM protein. Although these results provided basic knowledge on the impacts of dietary tributyrin supplementation alteration on the intestinal microbiota composition and diversity of juvenile yellow drum, putative involvement of bacteria in the metabolism and immunity merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The acyl-CoA ligase ( pegE ) catalyzes the ligation of PEG-carboxylate (polyoxyethylenate) and CoA on the cytoplasmic membrane [32]. We have identified homologs of PEG dehydrogenase ( pegA ), PEG-aldehyde dehydrogenase ( pegC ), acyl-CoA ligase ( pegE ), and AraC-type transcription regulator ( pegR ) in corynebacteria and mycobacteria genomes by sequence homology searches ( in silico analysis).…”
Section: Discussionmentioning
confidence: 99%
“…A gene coding acyl-CoA synthetase in the peg operon was expressed and the recombinant enzyme was found to react with PEG-carboxylate to form PEG-carboxylate-CoA. 28) Judging from the nature of this kind of protein (located on the cytoplasmic membrane as a translocator), the enzyme might be responsible for the translocation of PEG-carboxylate from the periplasm into the cytoplasm or for the detoxification of strong acidity of the substrate. Since glutathione S-transferase (a gene coding this enzyme is located in the downstream of the peg operon) is localized in the cytoplasm and suggested to buffer the toxicity of PEG-carboxylateCoA, 29) the role of acyl-CoA synthetase might be to buffer the toxicity of PEG-carboxylate (perhaps a low molecular size) together with glutathione S-transferase.…”
Section: Microbial Degradation Of Synthetic Water-soluble Polymersmentioning
confidence: 99%
“…All the metabolic enzymes included in PEG degradation have been localized in the membrane and are thought to work in the periplasm, in accordance with the fact that PEG and its metabolites were detected in the periplasmic fraction (unpublished data), suggesting that PEG is taken up into the periplasm and metabolized there. We cloned the genes involved in PEG degradation, and found that the peg operon consisted of five genes and was expressed by PEG through induction of an araCtype regulator, [26][27][28] as shown in Fig. 2.…”
Section: Microbial Degradation Of Synthetic Water-soluble Polymersmentioning
confidence: 99%